2018
DOI: 10.1016/j.rser.2017.06.086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the global media image of solar power

Abstract: This paper analyses the media image of solar power in order to understand the recent technology development trends. The increase in both solar PV panels as well as concentrated solar power plants has been influenced by decrease in solar power price, as well as subsidies and general public acceptance. This paper focuses on the latter, through quantitative media analysis. This paper utilises a modern method for media sentiment analysis from both editorial and social media, learning machine based analysis includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The issue of sustainable energy has been a case in point-several decades of media coverage of the expected dramatic consequences of a changing climate have engendered relatively little action to address the problem. Indeed, this disconnect between news coverage and public action casts doubt upon a notion of news coverage as -collections‖ of texts and images that are received and digested by the public; rather, its content is a mediation of a social relationship, co-constructed by creators and consumers and their norms and cultural perspectives (Nuortimo et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of sustainable energy has been a case in point-several decades of media coverage of the expected dramatic consequences of a changing climate have engendered relatively little action to address the problem. Indeed, this disconnect between news coverage and public action casts doubt upon a notion of news coverage as -collections‖ of texts and images that are received and digested by the public; rather, its content is a mediation of a social relationship, co-constructed by creators and consumers and their norms and cultural perspectives (Nuortimo et al, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Numerous studies having demonstrated that news media reflect and influence agendas and attitudes (Mohamed & Idid, 2019). Research also suggests that news media play a key role in the diffusion of new technologies into mainstream society (Nuortimo, Härkönen, & Karvonen, 2018;Wok & Mohamed, 2017). When writing news articles, journalists contextualize global and general issues such as sustainable energy to provide local meaning and relevance for their readership.…”
Section: Introductionmentioning
confidence: 99%
“…Brand experience relates to sensations, feelings, cognitions and behavioural responses evoked by brand-related stimuli, made up of a brand's design and identity, packaging, communications and environment (Brakus et al, 2009). Previous studies have applied sentiment analysis to online reputation management (Olaleye et al, 2018), to improve energy sector-related decision-making (Nuortimo and Harkonen, 2019), and to analyse the media image of different technologies (Nuortimo et al, 2017) to give some examples. The related data-driven analytics and decision-making have also been discussed (Krishen and Petrescu, 2019).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…This study understands that certain logic may apply but does not take a position on or try to assume the logic. Opinion mining and media sentiment analysis, in general (Ahmed et al, 2015;Chaudhary et al, 2018;Nuortimo et al, 2017;Nuortimo and Harkonen, 2019;Olaleye et al, 2018), are provided with support by introducing a new application. This study is in line with Dhaoui et al (2017) and Wang et al (2012) in understanding how manual analysis is not viable.…”
Section: Scientific Implicationsmentioning
confidence: 99%
“…It might also be necessary to differentiate between the types of media communication and their specific influence as the nature of media, selectivity of media use by the public, or the properties of media may play a role in whether the media effect is indirect, conditional and transactional (Valkenburg et al 2016). The public image of some renewable technologies, such as the solar power and biomass power have been attempted to clarify (Nuortimo et al 2017;2018a).…”
Section: Introductionmentioning
confidence: 99%